A Glutathione‐Activated Phthalocyanine‐Based Photosensitizer for Photodynamic Therapy. Issue 21 (15th April 2014) - He, Hui; Lo, Pui‐Chi; Ng, Dennis K. P.
Abstract Invited for the cover of this issue is the group of Dennis Ng at The Chinese University of Hong Kong. The image depicts the interaction of a molecular phthalocyanine‐quencher dyad with glutathione, resulting in detachment of the quencher, enhancement of fluorescence, and generation of singlet oxygen. The "activation" has also been demonstrated in tumor‐bearing nude mice. Read the full text of the article at 10.1002/chem.201400001.